Cognitive Tools of Management Consulting - Karayev, Robert A. (Advances in Social Sciences Research Journal, 2017)
The paper points out the challenges of management consulting in modern complex and unstable economic conditions. The authors emphasize the need for management consulting support tools that would be adequate to the hyper-turbulent nature of modern business environment and consider the possibility of developing such tools based on the ideas and methods of cognitive modeling. Examples of the use of cognitive tools are given and their prospective applications are discussed, such as the possibility of interdisciplinary integration in a compact and generally accessible form of “best support practices”, the possibility of studying the strategic prospects of enterprises in multifactor, dynamic and uncertain environments, the possibility of creating unified technological platform (engineering) of the “cognitive school” of strategic management.